Tolerogenic dendritic cells in type 1 diabetes: no longer a concept - Giannoukakis, Nick (Frontiers in Immunology, 2023)
Tolerogenic dendritic cells (tDC) arrest the progression of autoimmune-driven dysglycemia into clinical, insulin-requiring type 1 diabetes (T1D) and preserve a critical mass of  cells able to restore some degree of normoglycemia in new-onset clinical disease. The safety of tDC, generated ex vivo from peripheral blood leukocytes, has been demonstrated in phase I clinical studies. Accumulating evidence shows that tDC act via multiple layers of immune regulation arresting the action of pancreatic  cell-targeting effector lymphocytes. tDC share a number of phenotypes and mechanisms of action, independent of the method by which they are generated ex vivo. In the context of safety, this yields confidence that the time has come to test the best characterized tDC in phase II clinical trials in T1D, especially given that tDC are already being tested for other autoimmune conditions. The time is also now to refine purity markers and to “universalize” the methods by which tDC are generated. This review summarizes the current state of tDC therapy for T1D, presents points of intersection of the mechanisms of action that the different embodiments use to induce tolerance, and offers insights into outstanding matters to address as phase II studies are imminent. Finally, the inter-relationship of tDC and T-regulatory cells (Tregs) for survival, induction, and maintenance of a tolerogenic state that manages the underlying diabetes autoimmunity raises the possibility to co-administer or even to serially-administer tDC together with Tregs as a cellular co-therapy, enabling the best possible outcomes.